Принципы построения и особенности функционирования интеллектуальной системы обучения - Карасюк, В. В.; Гвозденко, М. В. (НТУ "ХПИ", 2012)
В статье предлагается решение задачи построения знаниеориентированной системы обучения в области правоведения на основе онтологических принципов. Показана структура базы знаний, для ее описания используется графовая модель. Отмечены особенности коллективной работы над онтологией. Определено, что система при коллективной работе имеет черты самоорганизованной. Ил.: 1. Библиогр.: 12 назв.

The article proposes a solution of the problem of constructing knowledge-oriented education system in the field of law, based on ontological principles. The structure of the knowledge base is shown and the description of the knowledge base is performed using graph model. An opportunity of teamwork with the ontology is described. It was determined that the information system for the teamworking have a self-organized features. Figs: 1. Refs: 12 titles.
Principles of construction and features of functioning the intellectual training system
Keywords: электронное образование; правоведение; знаниеориентированная система; онтология; графовая модель; jurisprudence; intellectual departmental teaching; ontology; count model